Sustainable Adoption And Implementation In Collaborative Enterprise: A Systematic Literature Review - Jnr, Bokolo Anthony; Mazlina, Abdul Majid; Awanis, Romli (JATIT, 2017)
Human life is reliant upon the natural environment, which, most would agree, is rapidly degrading; presently one of the most difficult problems that humanity faces is the sustainable development of our society, i.e. how to meet the needs of the present without compromising the ability of future generations to meet their own needs. The sustainable enterprise is one that contributes to sustainable development by simultaneously delivering economic, social, and environmental benefits. Sustainability has been increasingly becoming a tactical consideration for developing Green practices through balancing social, economic and environmental performance of collaborative enterprise (CE). As the perceived importance of eco-sustainability has grown, there has been increasing discussion on both eco-sustainable solutions. An understanding of the process, variables and related attributes that influence CE to adopt and implement sustainable practices may contribute in creating a Green CE. Presently there are a few Green ITIS and sustainability review paper published, however none of these review papers aimed at exploring Green process, variables (independent, moderating, mediating, control and dependent) and their related attributes in relation to adoption and implementation of Green practices in CE. Thus to get a clear understanding of how practitioners and decision makers implement and adopt sustainable practice in CE, this paper carries out a systematic literature review to investigate existing research in the domain of Green ITIS and sustainability in CE. Findings from this paper show that existing models and frameworks are limited with the capability to support IT practitioners to make strategic decision on how to implement and adopt Sustainable practice in CE. This paper also shows the Green ITIS process, variables and their related attributes to be considered in going Green in CE. Existing Sustainable models and frameworks developed in CE previously was also explored. Lastly the discussion, contribution, limitation, implication of the study, conclusion and future work is stated.